The Major Surface Glycoprotein of Pneumocystis murina Does Not Activate Dendritic Cells - Sassi, Monica (J Infect Dis, 2018)
The major surface glycoprotein (Msg) is the most abundant surface protein among Pneumocystis species. Given that Msg is present on both the cyst and trophic forms of Pneumocystis and that dendritic cells play a critical role in initiating host immune responses, we undertook studies to examine activation of bone marrow–derived myeloid dendritic cells by Msg purified from Pneumocystis murina. Incubation of dendritic cells with Msg did not lead to increased expression of CD40, CD80, CD86, or major histocompatibility complex class II or to increased secretion of any of 10 cytokines. Microarray analysis identified very few differentially expressed genes. In contrast, lipopolysaccharide-activated dendritic cells had positive results of all of these assays. However, Msg did bind to mouse mannose macrophage receptor and human DC-SIGN, 2 C-type lectins expressed by dendritic cells that are important in recognition of pathogen-associated high-mannose glycoproteins. Deglycosylation of Msg demonstrated that this binding was dependent on glycosylation. These studies suggest that Pneumocystis has developed a mechanism to avoid activation of dendritic cells, potentially by the previously identified loss of genes that are responsible for the high level of protein mannosylation found in other fungi.